2019
DOI: 10.2147/ijgm.s230054
|View full text |Cite
|
Sign up to set email alerts
|

<p>Out Of Hospital And In Hospital Management Of Cellulitis Requiring Intravenous Therapy</p>

Abstract: BackgroundCellulitis requiring intravenous therapy can be managed via out of hospital programs, but a high number of patients are still admitted to hospital.ObjectiveWe aimed to review the clinical features, management and outcomes of patients with cellulitis requiring intravenous therapy in a Hospital in the Home (HITH) program compared to patients who are admitted to hospital.MethodsA prospective cohort study of patients with limb cellulitis requiring intravenous antibiotics was conducted at a metropolitan p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Similar practice has also been reported outside the Scandinavian countries [27]. To consider such therapy as over-treatment is debateable in our setting, although increasing knowledge supports use of oral antimicrobial therapy or outpatient intravenous therapy in such cases [28,29]. A disadvantage of early outpatient therapy is that it frequently involves more broad-spectrum drugs.…”
Section: Discussionmentioning
confidence: 52%
“…Similar practice has also been reported outside the Scandinavian countries [27]. To consider such therapy as over-treatment is debateable in our setting, although increasing knowledge supports use of oral antimicrobial therapy or outpatient intravenous therapy in such cases [28,29]. A disadvantage of early outpatient therapy is that it frequently involves more broad-spectrum drugs.…”
Section: Discussionmentioning
confidence: 52%
“…Patients admitted to hospital could be more unwell and likely to suffer from complications but also have a higher CCI. 12 Further work is needed to understand the differences between ED and ward referrals, but our data suggest that expanding the pool of ED referrals may be safe and effective.…”
Section: Discussionmentioning
confidence: 87%
“…Eleven studies, including those treated as outpatients/OPAT, reported an average length of IV therapy of 2-7 days and an average overall treatment duration of 6-10 days. [59][60][61][62][63][64][65][66][67][68][69] Clinical response rates ranged from 85-97%, failure rates from 5-22% and recurrence rates from 0-6%.…”
Section: Evidence For Overall Duration Of Therapymentioning
confidence: 99%
“…In studies comparing patients with better versus worse outcomes, groups with poorer outcomes had higher proportions of patients with prior cellulitis, sepsis at presentation and comorbidities (including diabetes, immunosuppression, obesity and venous insufficiency). 40,48,50,55,60,62 With regards to treatment-associated harms, data on adverse events were not reported separately for cellulitis patients within SSTI trials, but overall, three trials found a higher incidence of gastrointestinal side-effects among patients receiving longer treatment (linezolid and erythromycin) versus shorter treatment (tedizolid and azithromycin). 29,32,33 One trial found no difference in gastrointestinal side effects between groups.…”
Section: Evidence For Overall Duration Of Therapymentioning
confidence: 99%